The Implications of Technological Change for Collective Bargaining - Fryer, John (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1967)
In the following article, the author tries to demonstrate how collective bargaining is likely to remain the corners-tone of our industrial relations system in developing successful adjustment programmes to cope with technological change. He underlines also some necessary change in bargaining attitudes.